KEBIJAKAN POLITIK NEGARA DALAM SISTEM DAFTAR TUNGGU HAJI DI INDONESIA (STUDI KASUS KOTA DENPASAR) - hadirman hadirman hadirman; zulkarnain nasution (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2021)
State political policy in the hajj waiting list system is manifested in the forma of state intervention ini religious life through regulation. The goverment ini this case carries out power politics while maintaining political stability. The state through the Minsitry of Religion has monopolized the implementation of the hajj because it is fully involved in the regulatory, operational and execution stages in the field. The motive for this policy is to expand power through the reproduction of power thorugh an ideological system of regulations and rules in order to control the strategic functions of the Ministry of Religion and is abudant with funding resources for the state amd political parties. This study aims to explain the factors that cause the existence of state politics in the hajj waiting list system. The reseach locations in the city of Denpasar, wich has the largest number ini Bali Province. This research used qualititave methods. The analysis used is critical theory. The results of this study reveal the factors causing state politics the hajj waiting list system, including: (1) state politics and ideology; (2) party politics and ideology; (3) the leviathan of state power in religious life; and (4) polical stability.